Human Capital Strategy and Organizational Performance: an AMO-Based Case Study of a Regional Development Bank - Rajab, Ridwan; Rizki, Muhammad (Management Department, Universitas Islam Negeri Alauddin Makassar, Indonesia, 2025)
Performance disparities in Regionally Owned Enterprises persist despite substantial investment in human capital development, raising questions about how workforce strategies translate into measurable organizational outcomes. This study advances an integrated AMO-based human resource development model, positioning ability, motivation, and opportunity as structurally aligned drivers of performance in regional banking. Using a descriptive qualitative design, data were obtained from interviews and institutional documents to examine how development architecture shapes operational effectiveness at Bank Sulselbar, Indonesia. Findings indicate that competency-based training strengthens ability, structured performance targets reinforce motivation, and formalized career management institutionalizes opportunity through aligned succession pathways. These interdependent mechanisms produce systemic workforce readiness rather than isolated skill enhancement. For banking executives, the evidence affirms that sustained performance improvement requires designing human resource systems as integrated strategic infrastructure, where training, appraisal, and career mobility operate as a coherent capability-building ecosystem embedded in governance.